Applications of Power Ultrasound in Mining - Gaete-Garreton, L; Vargas-Hernandez, y (Elsevier, 2023)
This chapter deals with the application of power ultrasound in the mining industry. It includes an overview of mining operations and four sections covering: the in-situ determination of rock mass stress condition by ultrasound for rock stability analysis, the use of power ultrasound to assist ore particle size reduction, application of power ultrasound in flotation concentration, and the use of power ultrasound in particle sedimentation for enhancement of water recovery. The application of power ultrasound for testing the rock mass stress state involves the use of continuum intense waves to penetrate a significant depth into the rock and detect changes of the stress state. Ore particle size reduction—crushing and grinding—is the most expensive operation in the production of ore minerals due to intensive energy consumption and wear of steel grinding components. Both factors can be improved by using power ultrasound technology. Power ultrasound in flotation concentration has found attractive applications in the last decades. Laboratory studies have reported improvements in flotation due to slime coating removal, oxidation film removal, small bubble generation, and other effects. Finally, the water-solid separation by gravitational methods has become a critical issue in the mining industry; ultrasound-assisted sedimentation is explored as an attractive industrial application. In summary, this chapter aims to show the progress made with the introduction of power ultrasound in the mining industry. © 2023 Elsevier Ltd. All rights reserved.